2022
DOI: 10.3390/ijpb13030026
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils of Tagetes minuta and Lavandula coronopifolia from Djibouti: Chemical Composition, Antibacterial Activity and Cytotoxic Activity against Various Human Cancer Cell Lines

Abstract: The chemical composition of the essential oils of two plants (Tagetes minuta L. and Lavandula coronopifolia L.) harvested from the Day region (in the north of Djibouti) is the subject of this study. The extraction of essential oils was carried out by hydrodistillation, and the average yield was obtained at a rate of approximately 0.25% for Tagetes minuta L. and 0.42% for Lavandula coronopifolia L. The analyses of these essential oils by gas chromatography coupled with mass spectrometry identified 13 compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Analyses of cyclohexane extract (Table 3) demonstrated the presence of nine compounds, of which four were already identified in our essential oil (perilla aldehyde, o-cymene, 3-carene, and terpinen-4-ol). Furthermore, we found in this extract: thiocarbamic acid, N,N-dimethyl-S-1,3-diphenyl-2-butenyl ester, identified in the methanol extract of wild mushroom [14], 9-octadecenoic acid, (2-phenyl-1,3-dioxolan-4-yl)methyl ester, cis, which was already identified in Lavandula coronopifolia essential oil [15], and D-verbenone [16]. Thymol was identified in methanol extract; it was also identified in the essential oil of A. pusilla [3].…”
Section: Profile Of the Molecular Composition Of A Pusilla Extracts B...mentioning
confidence: 54%
“…Analyses of cyclohexane extract (Table 3) demonstrated the presence of nine compounds, of which four were already identified in our essential oil (perilla aldehyde, o-cymene, 3-carene, and terpinen-4-ol). Furthermore, we found in this extract: thiocarbamic acid, N,N-dimethyl-S-1,3-diphenyl-2-butenyl ester, identified in the methanol extract of wild mushroom [14], 9-octadecenoic acid, (2-phenyl-1,3-dioxolan-4-yl)methyl ester, cis, which was already identified in Lavandula coronopifolia essential oil [15], and D-verbenone [16]. Thymol was identified in methanol extract; it was also identified in the essential oil of A. pusilla [3].…”
Section: Profile Of the Molecular Composition Of A Pusilla Extracts B...mentioning
confidence: 54%
“…In the specific context of the utilization of Djibouti's essential oils in cancer treatments, Principal Component Analysis (PCA) serves as a mathematical tool aimed at unraveling intricate interdependencies among diverse parameters. The primary aim within this framework was to effectively visualize and consolidate data concerning the efficacy of IC50 values, as previously referenced, pertaining to Djibouti's essential oils, along with vinblastine, doxorubicin, combrestatin A4, and monomethylauristatin E [19][20][21][22]. This endeavor was carried out to highlight divergences in values observed across the tested cancer cell lines, thereby facilitating a concise and comprehensible presentation.…”
Section: Discussionmentioning
confidence: 99%
“…With this perspective in mind, our study focused on evaluating the therapeutic potential of seven essential oils extracted from local medicinal plants in Djibouti as potential treatments against cancer. To provide context to our research, we compared these extracts to active compounds commonly used in cancer treatment protocols [19][20][21][22].…”
Section: Use Of Essential Oils From Djibouti In Cancer Treatments (In...mentioning
confidence: 99%
“…Although significant progress has been made in comprehending the mechanisms of cell transformation, cancer continues to pose a significant global health challenge, primarily due to the emergence of multidrug resistance (MDR) in transformed cells. Cellular plasticity and flexibility, as well as high exposure to anticancer drugs, make tumors resistant [ 53 , 54 , 55 , 56 ]. EOs whose antitumor properties have been known since antiquity through empirical studies, have been the subject of numerous publications confirmed by in vitro studies, showing their cytotoxic action against different tumor cell lines ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%